1991
DOI: 10.1104/pp.97.3.1017
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Storage Proteins in Poplar

Abstract: Bark, wood, and root tissues of several Populus species contain a 32-and a 36-kilodalton polypeptide which undergo seasonal fluctuations and are considered to be storage proteins. These two proteins are abundant in winter and not detectable in summer as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and immunodetection. An antibody raised against the 32-kilodalton storage protein of Populus trichocarpa (T. & G.) cross-reacts with the 36-kilodalton protein of this species. The synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…7). This protein band corresponds in size to VSP previously characterized in poplar bark (Coleman et al, 1991;Langheinrich & Tischner, 1991). The comparison between stained SDS-PAGE gels from control and transgenic plants showed that the 32-kDa polypeptide accumulated in transgenic stems more quickly than in control plants (Fig.…”
Section: Tree Growth and Gs1 Content In Leafmentioning
confidence: 99%
“…7). This protein band corresponds in size to VSP previously characterized in poplar bark (Coleman et al, 1991;Langheinrich & Tischner, 1991). The comparison between stained SDS-PAGE gels from control and transgenic plants showed that the 32-kDa polypeptide accumulated in transgenic stems more quickly than in control plants (Fig.…”
Section: Tree Growth and Gs1 Content In Leafmentioning
confidence: 99%
“…Furthermore, the stored nitrogen compounds have been suggested to be mainly used in supporting new shoot growth and development in the following spring while the nitrogen compounds from root absorption in the current year are used for tree growth in later seasons (Stepien et al 1994). Although VSPs have been identified in the vegetative organs of several temperate trees (van Cleve et al 1988;Wetzel et al 1989;Clausen and Apel 1991;Langheinrich and Tischner 1991;Stepien and Martin 1992;Coleman 2001a, 2001b), their seasonal fluctuation was assumed to be similar to that of the other so-called stored nitrogen compounds as above (Wetzel et al 1989). On the basis of this assumption, external factors such as nitrogen application, low temperature and short days play an important role in regulating VSP accumulation (Clausen and Apel 1991;Langheinrich and Tischner 1991;Coleman et al 1991Coleman et al , 1992Coleman and Chen 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The external factors, such as low temperature and short days, have been emphasized as key signals in inducing VSP accumulation in trees (Causen and Apel 1991;Langheinrich and Tischner 1991;Coleman et al 1991Coleman et al , 1992Coleman and Chen 1993). Recently, we found that the seasonal fluctuation of VSPs was very similar between the tropical tree S. macrophylla and the temperate tree Populus canadensis, suggesting that this seasonal fluctuation pattern in the whole tree might be an important mechanism by which the trees regulated their growth (Tian et al 2003(Tian et al , 2005.…”
mentioning
confidence: 86%
See 2 more Smart Citations